2021
DOI: 10.1021/acs.iecr.1c01392
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility Process of Hydrocarbon Mixture Gas and Crude Oil: Insights from Molecular Dynamics

Abstract: Using molecular dynamics simulations, we investigate the miscibility process of hydrocarbon mixture gas and crude oil in Tarim Oilfield, which was not well understood from the microscopic points of view. The results show that the increase of the pressure of hydrocarbon mixture gas is favorable for the gas−oil miscibility until the interfaces vanish under a minimum miscible pressure (MMP). The identified MMP (37.3 MPa) is well consistent with the experimental value. With increasing gas pressure, the parallel di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…The substrate is constrained, and the polar functional groups and ions move in an NVT ensemble during calculations. The grids are divided in the z -direction of the whole system with an interval distance of 0.02 nm, and the number of samples per grid is set to 40 . In the PMF curves, the deeper the potential wells are, the more attractive the substrate with molecules and ions is.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The substrate is constrained, and the polar functional groups and ions move in an NVT ensemble during calculations. The grids are divided in the z -direction of the whole system with an interval distance of 0.02 nm, and the number of samples per grid is set to 40 . In the PMF curves, the deeper the potential wells are, the more attractive the substrate with molecules and ions is.…”
Section: Resultsmentioning
confidence: 99%
“…The grids are divided in the z-direction of the whole system with an interval distance of 0.02 nm, and the number of samples per grid is set to 40. 12 In the PMF curves, the deeper the potential wells are, the more attractive the substrate with molecules and ions is. Obviously, the substrate is more attractive to ions than to polar molecules; among them, the interaction between calcium ions and substrate is the strongest.…”
Section: Distribution Of Polar Molecules and Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing shale oil recovery through fluid injection into shale reservoirs has emerged as a prominent research topic in recent years. A large number of studies , have shown that gas injection is an efficient method to enhance unconventional oil recovery in low permeability shale reservoirs because of its better injectivity and higher sweep efficiency. ,, CO 2 , N 2 , and natural gases are commonly used for injection, in which CO 2 has gained more attention due to its advantages, such as low minimum miscibility pressure . Enhancing shale oil recovery by injecting CO 2 is recognized as a remarkable technology and has attracted higher attention lately, not only because of conquering the energy resource exploitation problems, but also for the possibilities achieving CO 2 storage .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations, in conjunction with experimental techniques, provide powerful methods to study the dynamics, structure, and energetic properties of nanoscale systems, including those encountered in shale oil reservoirs. ,,, MD simulations have been effectively utilized to model fluids in diverse reservoir rocks, such as clays, quartz, carbonates, and kerogen . However, most of the existing research studies involve pure water or gas phase , replacement fluid; little attention has been paid to hybrid fluids.…”
Section: Introductionmentioning
confidence: 99%